Spider silk as an active scaffold in the assembly of gold nanoparticles and application of the gold-silk bioconjugate in vapor sensing - Singh, Amit; Hede, Shantesh; Sastry, Murali (Small, 2007)
Spider silk is being viewed with interest by materials scientists due to its excellent resilience and mechanical properties. In this paper we show that spider silk is an excellent scaffold for the one-step synthesis and assembly of gold nanoparticles. Formation of a gold nanoparticle-spider-silk bioconjugate material is accomplished by simple reaction of the fibers with aqueous chloroauric acid. The gold nanoparticles thus formed are strongly bound to the spider-silk fiber surface enabling study of the electrical properties of the nano bioconjugate. Using the well-known contraction/expansion behavior of the fibers in solvents of varying polarity, we show that exposure of the gold nanoparticle-spider silk bioconjugate to vapors of methanol and chloroform leads to changes in electrical transport through the nanoparticles and thus, the possibility of developing a vapor sensor. The bioconjugate shows excellent response time and cycling efficiency to methanol vapors. The activation energy of electron transport from one gold nanoparticle to another in the nanobiocojugate was determined from temperature-dependent electron-transport measurements to be approximately 1.7 eV.
Keywords: bioconjugates; Gold; Nanoparticles; sensors; spider silk

Facile synthesis and gas sensing properties of nanotriangular tin oxide - Deshmukh, Rupali G.; Badadhe, Satish S.; Vaishampayan, Mukta V.; Mulla, Imtiaz S. (Materials Letters, 2008)
In the present study we report a simple and convenient chemical route using pentaerythritol as a structure-directing agent for the synthesis of crystalline nanotriangular SnO2. We propose the scheme for the formation of nanotriangular structures wherein the preliminary spherical nanocrystallites are formed due to the low surface energy associated with them. These spherical nanocrystallites grow into the various linear intermediate shapes like Y, bi and tripods, which finally lead to the triangles, pyramids and bipyramids. Such variation in the structure occurs due to the structure directing pentaerythritol. These polycrystalline SnO2 nanomaterials with structural peculiarities were tested for the gas sensing characteristics. Their response towards ethanol vapor, H-2 and LPG were investigated. It was found to exhibit high response towards ethanol vapors at the operating temperature of 250 degrees C. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Nanomaterials; Oxides; Semiconductors; sensors

Synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Materials Chemistry and Physics, 2008)
In the present investigation the synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial has been reported. The material was synthesized by coprecipitation process combined with surfactant incorporating method. The concentration level of Ce (III) additive was varied systematically from 1 to 11 wt.%. After calcinations at500 degrees C,a high BET surface area of 40 m(2)/g was obtained for 7 wt.% CeO2. The effect of variation of sintering temperature (600-800 degrees C/2h) on the particle size and surface area of a CeO2/SnO2 system was investigated. The material obtained was nanocrystalline, having particle size in the range of 10-16 nm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CeO2:SnO2; Nanomaterials; sensors

Quantum dot bio-conjugate: as a western blot probe for highly sensitive detection of cellular proteins - Kale, Sonia; Kale, Anup; Gholap, Haribhau; Rana, Abhimanyu; Desai, Rama; Banpurkar, Arun G.; Ogale, Satishchandra; Shastry, Padma (Journal of Nanoparticle Research, 2012)
In the present study, we report a quantum dot (QD)-tailored western blot analysis for a sensitive, rapid and flexible detection of the nuclear and cytoplasmic proteins. Highly luminescent CdTe and (CdTe) ZnS QDs are synthesized by aqueous method. High resolution transmission electron microscopy, Raman spectroscopy, fourier transform infrared spectroscopy, fluorescence spectroscopy and X-ray diffraction are used to characterize the properties of the quantum dots. The QDs are functionalized with antibodies of prostate apoptosis response-4 (Par-4), poly(ADP-ribose) polymerases and beta actin to specifically bind with the proteins localized in the nucleus and cytoplasm of the cells, respectively. The QD-conjugated antibodies are used to overcome the limitations of conventional western blot technique. The sensitivity and rapidity of protein detection in QD-based approach is very high, with detection limits up to 10 pg of protein. In addition, these labels provide the capability of enhanced identification and localization of marker proteins in intact cells by confocal laser scanning microscopy.
Keywords: Detection; Imaging; nanomedicine; quantum dot; Rapid; sensors; Western blot

Soft-sensor development for biochemical systems using genetic programming - Sharma, Suraj; Tambe, Sanjeev S. (Biochemical Engineering Journal, 2014)
Soft-sensors are software based process monitoring systems/models. In real-time they estimate those process variables, which are difficult to measure online or whose measurement by analytical procedures is tedious and time-consuming. In this study, the genetic programming (GP), an artificial intelligence based data-driven modeling formalism, has been introduced for the development of soft-sensors for biochemical processes. The novelty of the GP is that given example input-output data, it searches and optimizes both the form (structure) and parameters of an appropriate linear/nonlinear data-fitting model. In this study, GP-based soft-sensors have been developed for two bioprocesses, namely extracellular production of lipase enzyme and bacterial production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) copolymer. While in case study-I, the soft-sensor predicts the time-dependent lipase activity (U/ml), in case study-II it predicts the amount of accumulated polyhydroxyalkanoates (% dcw). The prediction and generalization performance of the GP-based soft-sensors was compared with the corresponding multi-layer perceptron (MLP) neural network and support vector regression (SVR) based soft-sensors. This comparison indicates that in the first case study the GP-based soft-sensor with the training and test set correlation coefficient (root-mean-squared-error) magnitudes of >0.96 (approximate to 0.962 U/ml) has clearly outperformed the two other soft-sensors. In case study-II involving bacterial copolymer production, the GP and SVR based soft-sensors have performed equally well (correlation coefficient approximate to 0.98) while the MLP based soft-sensor's performance was relatively inferior (correlation coefficient approximate to 0.94). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Artificial intelligence; Batch processing; Bioprocess monitoring; Lipase; Modeling; sensors

Self-assembled vertically aligned gold nanorod super-lattices for ultra-high sensitive detection of molecules - Apte, Amey; Bhaskar, Prashant; Das, Raja; Chaturvedi, Smita; Poddar, Pankaj; Kulkarni, Sulabha (Nano Research, 2015)
We show that self-assembled vertically aligned gold nanorod (VA-GNRs) superlattices can serve as probes or substrates for ultra-high sensitive detection of various molecules. D-glucose and 2,4,6-trinitrotoluene (TNT) have been chosen as model systems due to their very low Raman cross-sections (5.6 x 10(-30) cm(2).molecule(-1).sr(-1) for D-glucose and 4.9 x 10(-31) cm(2). molecule(-1).sr(-1) for TNT) to show that the VA-GNR superlattice assembly offers as low as yoctomole sensitivity. Our experiment on mixed samples of bovine serum albumin (BSA) and D-glucose solutions demonstrate sensitivity for the latter, and the possible extension to real samples. Self-assembled superlattices of VA-GNRs were achieved on a silicon wafer by depositing a drop of solvent containing the GNRs and subsequent solvent evaporation in ambient conditions. An additional advantage of the VA-GNR monolayers is their extremely high reproducible morphology accompanied by ultrahigh sensitivity which will be useful in many fields where a very small amount of analyte is available. Moreover the assembly can be reused a number of times after removing the already present molecules. The method of obtaining VA-GNRs is simple, inexpensive and reproducible. With the help of simulations of monolayers and multilayers it has been shown that superlattices can achieve better sensitivity than monolayer assembly of VA-GNRs.
Keywords: Nanostructures; Raman spectroscopy; self-assemblies; sensors; superlattices

Binding selectivity of vitamin K3 based chemosensors towards nickel(II) and copper(II) metal ions - Patil, Amit; Lande, Dipali N.; Nalkar, Archana; (Gejji, Shridhar P.; Chakrovorty, Debamitra; Gonnade, Rajesh; Moniz, Tania; Rangel, Maria; Pereira, Eulalia; Salunke-Gawali, Sunita (Journal of molecular Structure, 2017)
The vitamin K3 derivatives 2-methyl-3-[(pyridin-2-ylmethyl)-amino]-1,4-naphthoquinone (M-1), 2-methyl-3-[(pyridin-2-ylethyl)-amino]-1,4-naphthoquinone (M-2), 2-methyl-3-((2-(thiophen-2-yl) methyl)amino)naphthalene-1,4-dione (M-3) and 2-methyl-3-((2-(thiophen-2-yl)ethyl)amino)naphthalene-1,4-dione (M-4) have been synthesized, characterized and studied for their chemosensor abilities towards transition metal ions. Crystal structures of M-1 to M-4 revealed a variety of N-H center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions. Minor variations in such interactions by chemical stimuli such as metal ions, results in change in color that can be visualized by naked eyes. It has been shown that electronic structure and H-1 NMR, vibrational as well as electronic spectra from the density functional theory agree well with the experiments. The metal ion binding in ethanol, ethanol-water and in mild base triethylamine brings forth recognizing ability of M-1 toward Ni2+ whereas M-2 exhibits large sensing ability for Cu2+ ion. Interestingly M-1 display varying metal ion binding specificity in different solvents with the association constant in ethanol being 11,786 M-1 for Ni2+ compared to 9462 M-1 for the Cu2+. A reversal in preferential binding of M-2 with the respective association constants being 4190 M-1 and 6370 M-1 is discernible. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone Molecular-structures; Anthraquinone; Aqueous-solution; Chemosensor; Crystal-structures; Cu(II); Derivatives; DFT; Fluorometric Chemosensors; hydrogen bonding; Naphthoquinone; pi-pi stacking; Recognition; sensors

Boron-conjugated pyrenes as fluorescence-based molecular probes and security markers - Wakchaure, Vivek Chandrakant; Das, Tamal; Babu, Sukumaran Santhosh (ChemPlusChem, 2019)
Boron-embedded aromatic hydrocarbons are a class of molecules known for their distinct electronic and/or optoelectronic properties and are thus suitable for many potential applications. Among those, boronic ester and acid containing molecules have been widely used for sensing and molecular recognition applications, respectively. We compared the sensing and molecular recognition properties of two boron-containing pyrene derivatives for fluoride and glucose sensing applications. The presence of four boronate ester groups enabled fluoride ion sensing at the mu M level. The boronic acid derivative is very selective towards glucose compared to other saccharides. Furthermore, we used the mechano-responsive fluorescence changes and self-assembly of these derivatives, respectively, for fluorescence-based inkless and ink (water)-based writing in invisible security labeling applications.
Keywords: boron; carbohydrates; mechanoluminescence; pyrene; sensors

Polymeric PEI/PEG coated optical fiber fabry-perot interferometer for CO2 detection - Pawar, Dnyandeo; Lo Presti, Daniela; Lemma, Enrico D.; Rainer, Alberto; Kumar, Ajay; Kanawade, Rajesh; Silvestri, Sergio; Schena, Emiliano; Massaroni, Carlo (IEEE Sensors Journal, 2024)
Monitoring carbon dioxide (CO2) gas is essential for numerous applications, but the detection of CO2 in miniaturized devices presents significant challenges. In this study, a polyethyleneimine/poly(ethylene glycol) (PEI/PEG) coated optical fiber Fabry-Perot interferometer (FPI) and its charge transfer process toward CO2 are investigated. Scanning electron microscopy and Fourier transform infrared spectroscopy were used to analyze the surface morphology and vibration bands of the PEI/PEG composite. The PEI/PEG composite Fabry-Perot (FP) cavity of length similar to 13 mu m is coated at the distal end of the single-mode fiber using a dip coating technique. A highly sensitive optical and low-cost FPI probe fabrication has displayed a linear sensitivity of 17.10 nm/% in the range of 0.31%-1.25% CO2 gas. The response and recovery times of the sensor are in a few tens of seconds. The enhanced performance of the sensor is primarily due to the protonation and charge transfer between CO2 gas molecules and PEI/PEG composite. Due to low-cost fabrication and high sensitivity, this FPI sensor can be used in a range of potential applications in bioprocessing, healthcare, and environmental monitoring.
Keywords: dip coating; Fresnel's reflection; Interference; monitoring; Optical fiber sensors; Optical fibers; polymer composite; Polymers; refractive index; sensitivity; Sensor phenomena and characterization; sensors; swelling; Temperature sensors